Analisa pengaruh kuat arus hasil pengelasan GMAW terhadap kekerasan material ASTM A 36 - Juwanda Juwanda; Saifuddin Saifuddin; Marzuki Marzuki (Politeknik Negeri Lhokseumawe, 2021)
GMAW welding is a welding process that uses CO2 gas as a protective medium for weld metal from the influence of outside air. This welding uses a heat source from electrical energy which is converted or converted into heat energy. While ASTM A 36 steel plate is steel that has a carbon content of 0.30% so it is classified as low carbon steel. This steel is widely used in the market because it has many advantages, one of which has good welding properties (machinability), good wear resistance (wear) and good mechanical properties as well. This study aims to determine the hardness value of the welding results using the hardness test method in the GMAW welding process to ASTM A 36 steel with a 60̊ V angle seam. The variations of the currents used in this welding process are 80,100 and 120 Amper. From the tests that have been done, it is known that the lowest hardness strength at current 80 produces a hardness value of 65.60 Hrc. Meanwhile, the highest hardness value at 100 Amper flow obtained a hardness value of 80.40 HRC